The Use of Natural Curing on Beef Products - Eko Saputro (Indonesian Center for Animal Research and Development, 2016)
Efforts to control meat spoilage, safety and palatability in the production of meat products become essential for humans. These control efforts should keep good quality of meat products at ambient temperature. Curing using NaNO2 is one of meat preservation techniques. However, the Indonesian Agency for National Standardization prohibits the use of sodium nitrite (NaNO2) in the organic food production process due to its negative effect on health and food safety. Therefore, substitutes of NaNO2 as natural curing agent and supported technologies have to be found. This article discusses the curing process using curing agents in the form of nitrate from natural resources and a starter culture for reducing nitrate to nitrite. The addition of accelerators in the form of reductant and acidulant from natural or organic resources is also required to enhance curing process. Natural curing processes of beef products have been proven to produce similar meat quality of sensory, physico-chemical, and microbiological characteristics with curing process using NaNO2.